What is the Modern Human Eating? Dietary Transition of the Age-Old to the Modern Man of India - Daisy A. John; Giridhara R. Babu (Frontiers Media S.A., 2022)
Objectives: The objective of this review is to examine the changes in food consumption pattern of Indians over the years and to recommend evidence-based policy making regarding all the factors affecting food consumption.Methods: We have reviewed the articles from major databases such as PubMed and Google Scholar. The keywords used for the search included dietary pattern, dietary trend, dietary intake, food system, nutrition system, prehistoric food systems, drought, famine, whole grains, diets, prices, income, environment, urban food consumption, processed foods, food security, food preferences, demographic transition, fat intake, food production, public distribution system, food consumption pattern, Indian agriculture, and India.Results: There is no facilitating environment for the production and cultivation of healthy and sustainable food.Conclusion: Policymakers should make major amendments to food and agricultural policies, and demotivate the consumption of junk food.